2024
DOI: 10.1002/mc.23686
|View full text |Cite
|
Sign up to set email alerts
|

Silencing lncRNA‐DARS‐AS1 suppresses nonsmall cell lung cancer progression by stimulating miR‐302a‐3p to inhibit ACAT1 expression

Ji Li,
Yizhuo Li,
Xiaodan Sun
et al.

Abstract: Long noncoding RNAs (LncRNAs) have been gaining attention as potential therapeutic targets for lung cancer. In this study, we investigated the expression and biological behavior of lncRNA DARS‐AS1, its predicted interacting partner miR‐302a‐3p, and ACAT1 in nonsmall cell lung cancer (NSCLC). The transcript level of DARS‐AS1, miR‐302a‐3p, and ACAT1 was analyzed using qRT‐PCR. Endogenous expression of ACAT1 and the expression of—and changes in—AKT/ERK pathway‐related proteins were determined using western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…ACAT1 predominantly signals through inhibition of PDC by PDP1 and PDHA acetylation to enhance glycolysis and tumor growth, indicating the ACAT1-PDP1-PDHA axis a promising anti-cancer target ( 46 ). lncRNA DARS-AS1 inhibition attenuated non-small cell lung cancer development by activating miR-302a-3p to inhibit ACAT1 expression ( 47 ). It has been demonstrated that Kras-specific antigenic peptides in combination of avasimibe could promote CD8+ T cell infiltration and impair lung tumor progression ( 48 ).…”
Section: Acat1 and Lung Cancermentioning
confidence: 99%
“…ACAT1 predominantly signals through inhibition of PDC by PDP1 and PDHA acetylation to enhance glycolysis and tumor growth, indicating the ACAT1-PDP1-PDHA axis a promising anti-cancer target ( 46 ). lncRNA DARS-AS1 inhibition attenuated non-small cell lung cancer development by activating miR-302a-3p to inhibit ACAT1 expression ( 47 ). It has been demonstrated that Kras-specific antigenic peptides in combination of avasimibe could promote CD8+ T cell infiltration and impair lung tumor progression ( 48 ).…”
Section: Acat1 and Lung Cancermentioning
confidence: 99%